Research on factors affecting the development of sustainable community tourism in Thai Nguyen province, Vietnam – An approach from the perspective of the local community - Nguyen, Nam Danh; Uong, Lan Ngoc Thi (International Journal of Innovative Research and Scientific Studies, 2025)
The study aims to explore the factors affecting sustainable community tourism development in Thai Nguyen province in Vietnam from the perspective of the local community. Utilizing the Delphi method and PLS-SEM quantitative analysis, results from 204 survey samples reveal that sustainable community tourism development in Thai Nguyen province is influenced by economic, socio-cultural, environmental, local community involvement, human resources, policy, attractiveness, and tourism carrying capacity. Economic, environmental, and socio-cultural factors play particularly crucial roles. This research contributes to the literature on sustainable community tourism development and offers valuable practical implications for local authorities and tourism enterprises in creating effective development policies.